Analisis Framing pemberitaan Tidak Berkibarnya Bendera Merah Putih di Upacara Penutupan Thomas Cup 2020 : Studi di cnn indonesia.com dan pikiran rakyat. com - Nabila Prajna Paramita; hari wiryawan; Erwin Kartinawati (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2022)
In this research, researchers used qualitative research methods. This study aims to describe the framing of news in the news of the Red and White Flag Not Flying at the Closing Ceremony of the 2020 Thomas Cup after Indonesia won the Thomas Cup 2020 on CNN Indonesia.com and Mind Rakyat.com. In analyzing the news, the researcher uses Robert N. Entman's framing model analysis which focuses on the selection of issues and highlighting aspects. The results of this study indicate that the news presented by CNN Indonesia.com is more intense in reporting the incident. In selecting sources, CNN Indonesia.com tends to select people who are competent in this regard, such as LADI, Kemenpora, KOI, athletes, and badminton legends. So that the news is more objective and neutral in reporting the news about the not flying the Red and White flag at the closing ceremony of the 2020 Thomas Cup. Meanwhile, Mind Rakyat.com in reporting the event was not intense. In selecting its sources, Mind Rakyat.com tends to have a wider reach so that it is not only people who are competent in that field who can provide feedback regarding the events that occurred.